Nutrition sensitive food system: Policy analysis and investment framework for Myanmar - Babu, Suresh Chandra (International Food Policy Research Institute, 2019)
Ending malnutrition in all forms is a global development priority. Investment in nutrition can yield high returns in terms of reduced health costs, increased productivity and improved human resources capacity and economic growth (Covic & and Hendriks 2016; Shekar et al. 2017). Nutrition policy-making and program interventions in developing countries fail to bring together several sectors that contribute to nutrition improvement. Since food systems influence the type of food produced, understanding relevant drivers of a country’s food system with an emphasis on nutrition can help to end malnutrition (Per Pinstrup-Andersen 2012a; HLPE 2017; Babu and Kataki 2003). In this paper, we adopt a food systems perspective to review Myanmar’s current food system. With the help of a review of the literature and two national consultative stakeholder workshops, we examine Myanmar’s current food system. This is a crucial step since it identifies gaps existing in the current policies/ strategies being implemented. After the review, we developed an AIT (analyze gaps, identify priority investment areas, and track progress) operational framework that can be used to increase the nutrition-sensitivity of a food system. Applying this framework to Agriculture Development Strategy (ADS), this paper presents an analysis of the gaps that need to be addressed to make ADS nutrition-sensitive, provide priority investment areas, and a tracking system which monitors the progress of these investments.